An iPRES‐W Coil Array for Simultaneous Imaging and Wireless Localized B0 Shimming of the Cervical Spinal Cord. Issue 2 (25th April 2022) - Cuthbertson, Jonathan D.; Truong, Trong‐Kha; Stormont, Robert; Robb, Fraser; Song, Allen W.; Darnell, Dean
Abstract : Purpose: To develop a wireless integrated parallel reception, excitation, and shimming (iPRES‐W) coil array for simultaneous imaging and wireless localized B 0 shimming, and to demonstrate its ability to correct for distortions in DTI of the spinal cord in vivo. Methods: A 4‐channel coil array was modified to allow an RF current at the Larmor frequency and a direct current to flow on each coil element, enabling imaging and localized B 0 shimming, respectively. One coil element was further modified to allow additional RF currents within a wireless communication band to flow on it to wirelessly control the direct currents for shimming, which were supplied from a battery pack within the scanner bore. The RF signals for imaging were transferred via conventional wired connections. Experiments were conducted to evaluate the RF, B 0 shimming, and wireless performance of this coil design. Results: The coil modifications did not degrade the SNR. Wireless localized B 0 shimming with the iPRES‐W coil array substantially reduced the B 0 RMSE (−57.5% on average) and DTI distortions in the spinal cord. The antenna radiation efficiency, antenna gain pattern, and battery power consumption of an iPRES‐W coil measured in an anechoic chamber were minimally impacted by the introduction of a saline phantom representing tissue. Conclusion: The iPRES‐W coil array can perform imaging and wireless localized B 0 shimming of the spinal cord with no SNR degradation, with minimal change in wireless performance and without any scanner modifications or additional antenna systems within the scanner bore.